"They just say how stupid I was for being conned". Cyberscams and acquired brain injury: A qualitative exploration of the lived experience of survivors and close others. Issue 2 (7th February 2023) - Gould, Kate R.; Carminati, Jao-Yue J.; Ponsford, Jennie L.
ABSTRACT: Individuals with acquired brain injury (ABI) may be vulnerable to cyberscams due to their cognitive and psychosocial impairments. However, the lived experiences of cyberscam survivors with ABI and their close others is not understood, and no effective intervention has been identified. This qualitative study aimed to explore the perspectives of cyberscam survivors with ABI ( n  = 7) and their close others ( n  = 6). Semi-structured interviews explored the scam experience, impacts, vulnerabilities and interventions. Reflexive thematic analysis of interview transcripts identified seven themes: "who is at the helm?: vulnerabilities, " "the lure: scammer tactics, " "scammers aboard: scam experience, " "the discovery, " "sinking in: impacts, " "responding to the mayday: responses from others, " and "lifesavers: suggestions for intervention." The journey towards scam victimisation was complex, and complicated by the ABI. Cyberscams contributed to substantial financial disadvantage, loss of trust and shame. ABI related impairments and social isolation reportedly increased scam vulnerability and interfered with intervention attempts by family and professionals. Confusion, denial and disbelief created further barriers to discovery. The practical and emotional impacts on both cyberscam survivors with ABI and their family members, and a lack of effective intervention, highlight the need for increased education and awareness in order to improve online safety for those with ABI.